Application of Six Sigma methodology in the homogeneous nursing management for patients with acute pancreatitis (六西格玛管理法在急性胰腺炎患者同质化护理管理中的应用) - LYU Jian (吕健); ZHOU Qun (周群); WEI Yanli (魏艳丽); XIE Lan (谢岚) (中西医结合护理)
Objective To investigate the role of Six Sigma methodology in the homogeneous nursing management for patients with acute pancreatitis (AP). Methods Totally 21 AP patients who admitted to emergency room of the hospital between June 2018 and June 2020 were included as the control group. Since July 2020, the Six Sigma methodology was used in procedure improvement of the homogeneous nursing management for AP patients. Another 20 AP patients who admitted to emergency room of the hospital between July 2020 and June 2021 were included as the intervention group. Emergency nursing ability of emergency nurses was evaluated before and after implementation of Six Sigma methodology. Results Scores for assessment of emergency nursing ability and homogeneous management procedure increased significantly after implementation of Six Sigma methodology (P＜0. 01) . Conclusion Adopting the Six Sigma methodology in the homogeneous nursing management is potentially effective to enhance the emergency nursing ability of emergency nurses and improve the quality of emergency care for AP. (目的 探讨急诊抢救室应用六西格玛管理法在急性胰腺炎同质化护理管理流程中的作用。方法 选取2018年6月—2020年6月急诊抢救室收治的21例急性胰腺炎患者为对照组。2020年6月, 科室将六西格玛管理法用于急性胰腺炎同质化护理管理流程改进中, 选取2020年7月—2021年6月急诊抢救室收治的20例患者为干预组。评估和分析六西格玛管理法实施前和实施后急诊抢救室护士的急救护理能力。结果 实施六西格玛管理法后, 急诊抢救室护理人员急救护理能力评分和处置流程执行评分较实施前提高, 差异有统计学意义(P＜0. 01)。结论 运用六西格玛管理优化急性胰腺炎同质化护理管理流程, 有利于迅速提升不同能级护士的急救护理能力, 提升急救护理质量。)